Designing polarization management devices by tilting subwavelength grating structures - Luque-González, José Manuel; Herrero-Bermello, Alaine; Ortega-Moñux, Alejandro; Molina-Fernández, Íñigo; Velasco, Aitor V.; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Halir, Robert (My University, 2019)
Subwavelength gratings (SWG) are periodic structures which behave as controllable homogeneous metamaterials. SWGs are extremely interesting when they are used in platforms with a limited choice of material refractive indices, enabling the design of a myriad of high-performance devices. Here we present a novel technique to gain control over the intrinsic anisotropy of the synthesized metamaterial. We show that tilting the silicon segments in a SWG structure mainly affects the in-plane (TE) modes, with little impact on the out-of-plane (TM) modes. Moreover, we present a methodology to quickly but accurately calculate the modes of a tilted periodic structure modeling the structure as a rotated uniaxial crystal which can be solved with an anisotropic mode solver. Measurements on a set of fabricated tilted SWG waveguides validate our simulation results. By using the presented technique, we design a polarization beam splitter based on a 2x2 multimode interferometer. The design is based on the optimization of the tilting angle to tone the beat length of the TE modes to be a half of the beat length of the TM modes.
Keywords: Optica integrada; Materiales ópticos; Metamateriales; Integrated optics; Subwavelength structures; Anisotropic optical materials; Metamaterials